Effects of temperature and acetic acid on electrochemical corrosion behavior of steel X80 - Yadong Li; Wanpeng Yao; Siquan Wang; JianJun Pang; Yan Li (Corrosion Communications, 2025)
Effects of temperature and acetic acid (HAc) on corrosion behavior of steel X80 were investigated through electrochemical measurements, including electrochemical impedance spectroscopy and potentiodynamic polarization curves. Results show that corrosion current density of steel X80 increased with temperature. Near-surface pH values of steel X80 reveal that due to the formation conditions of the corrosion film, there were differences between the electrochemical and mass loss results. Changes in cathodic and anodic charge transfer resistance indicate that the mechanism for HAc effects on cathodic reaction was buffering, and HAc served as source of H+.